Improved magnetic equivalent circuit for dual stator consequent pole permanent magnet machine - Sapmaz, Tunahan; Oner, Yasemin (ELSEVIER, 2022)
This paper proposes a non-linear magnetic equivalent circuit (MEC) model for three different dual stator consequent pole permanent magnet (DSCP-PM) machines. It also includes both no-load and on-load electromagnetic performance criteria. The fundamental of the MEC model is that it takes into the influence of winding flux leakage and iron saturation consideration. Besides, winding magneto motive forces (MMF) of DSCP-PM machines are applied to model both distributed winding and concentrated winding. An iterative algorithm is applied to resolve the problem when magnetic steel is severely saturated. Furthermore, the modeling for DSCPPM machine provides a standard for modeling this machine. Finally, the MEC model's accuracy and practicality for DSCP-PM machine are validated by the finite element (FE) method.
Keywords: Analytical models; Magnetic equivalent circuit; Permanent magnet machines; Dual stator; FIELD DISTRIBUTION; DC MOTORS; ANALYTICAL-MODEL; HYBRID; Materials Science; Physics